The challenge of reconstructing the Phanerozoic sea level and the Pacific Basin tectonics - Ruban, Dmitry; Conrad, Clinton; van Loon, A.J. (Tom) (Geologos, 2011)
The relationships between the interior dynamics of our planet and global sea level can be unravelled when plate-tectonic reconstructions are available for the entire Earth. A review of global tectonics reveals significant deficiencies in our understanding of the geodynamic evolution of the Pacific (Panthalassa or Proto-Pacific) during the Cambrian-Jurassic time-span. This particular, but major, shortcoming presents a true challenge for modern geoscientists, who are encouraged to produce a detailed plate-tectonic reconstruction of the Pacific for the pre-Cretaceous in order to advance our understanding of Phanerozoic sea-level change. A set of approaches, including geological/geophysical modelling, investigation of accretionary prisms, palaeobiogeographical studies, and careful examination of eustatic sea-level changes, are proposed that will help geoscientists tackle the challenge of understanding how Pacific geodynamics affected global sea level during the Phanerozoic.